2016
DOI: 10.1002/jcb.25810
|View full text |Cite
|
Sign up to set email alerts
|

Popdc1/Bves Functions in the Preservation of Cardiomyocyte Viability While Affecting Rac1 Activity and Bnip3 Expression

Abstract: The Popeye domain containing1, also called Bves (Popdc1/Bves), is a transmembrane protein that functions in muscle regeneration, heart rate regulation, hypoxia tolerance, and ischemia preconditioning. The expression of Popdc1/Bves is elevated in cardiomyocytes maintained in serum free defined medium. We hypothesized that Popdc1/Bves is important for cardiomyocyte survival under the stress of serum deprivation and investigated the mechanisms involved. A deficit in Popdc1/Bves, achieved by siRNA-mediated gene si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Isolated cardiac myocytes from Popdc1 null mutants displayed altered Ca 2+ -transients and increased vulnerability to oxidative stress. Apparently Popdc1 is involved in myocyte survival through the suppression of the pro-apoptotic Bcl2 interacting protein 3 ( Bnip3 ) gene [ 62 ]. While skeletal muscle is not as well studied than cardiac muscle in POPDC null mutants, it has been shown that muscle regeneration is impaired in Popdc1 null mutants, however, the underlying molecular mechanism has yet to be elucidated [ 63 ].…”
Section: Animal Models To Define the Function Popdc Genesmentioning
confidence: 99%
“…Isolated cardiac myocytes from Popdc1 null mutants displayed altered Ca 2+ -transients and increased vulnerability to oxidative stress. Apparently Popdc1 is involved in myocyte survival through the suppression of the pro-apoptotic Bcl2 interacting protein 3 ( Bnip3 ) gene [ 62 ]. While skeletal muscle is not as well studied than cardiac muscle in POPDC null mutants, it has been shown that muscle regeneration is impaired in Popdc1 null mutants, however, the underlying molecular mechanism has yet to be elucidated [ 63 ].…”
Section: Animal Models To Define the Function Popdc Genesmentioning
confidence: 99%
“…Isolated cardiac myocytes from Popdc1 null mutants displayed impaired Ca + 2 -transients, increased vulnerability to oxidative stress and absence of pharmacologic preconditioning. Further studies using myocytes treated with Popdc1 siRNA revealed that Popdc1 is required for cardiac myocyte survival [62] . Loss of Popdc1 causes an increase in the expression of the proapoptotic BCL2 interacting protein 3 ( Bnip3 ), which may explain the increased vulnerability when null mutant hearts are subjected to ischemia/reperfusion injury.…”
Section: Discovery Of the Popeye Domain Containing (Popdc) Genesmentioning
confidence: 99%
“…Suppression of POPDC1 in myocytes cultured under serum-starved conditions was recently shown to result in cardiomyocyte cell death and the upregulation of Bnip3 [53]. Furthermore, POPDC1 was shown to regulate Bnip3 expression [53]. Interestingly, this is the first dataset linking suppression of POPDC1 to increased cell death and to mitochondrial-mediated mechanisms of regulating cell viability (Figure 3).…”
Section: Popdc1 and Bnip3mentioning
confidence: 78%
“…Suppression of POPDC1 in myocytes cultured under serum-starved conditions was recently shown to result in cardiomyocyte cell death and the upregulation of Bnip3 [53]. Furthermore, POPDC1 was shown to regulate Bnip3 expression [53].…”
Section: Popdc1 and Bnip3mentioning
confidence: 97%